Preparation and Evaluation of Novel In Situ Gels Containing Acyclovir for the Treatment of Oral Herpes Simplex Virus Infections. (24th March 2014) - Chaudhary, Binu; Verma, Surajpal
Abstract : The objective of this work was to develop an oral mucosal drug delivery system to facilitate the local and systemic delivery of acyclovir for the treatment of oral herpes infection caused by the herpes simplex virus (HSV). An in situ gelling system was used to increase the residence time and thus the bioavailability of acyclovir in oral mucosa. Temperature and pH trigged in situ gel formulations were prepared by cold method using polymers like poloxamer 407, carbopol 934, and HPMC. Glycerin and a mixture of tween 80 and ethanol (1 : 2 ratio) were used as the drug dissolving solvent. The pH of carbopol containing formulation was adjusted to pH 5.8 while the pH of poloxamer solution was adjusted to pH 7. These formulations were evaluated for sol-gel transition temperature, gelling capacity, pH, viscosity, spreadability, gel strength, drug content, ex-vitro permeation, and mucoadhesion. The gelation temperatures of all the formulations were within the range of 28–38°C. All the formulations exhibited fairly uniform drug content (98.15–99.75%). Drug release study of all the formulations showed sustained release properties. The release of drug through these in situ gel formulations followed the Higuchi model and Korsmeyer peppas model mechanism.